Generation of periodic signatures at Saturn through Titan's interaction with the centrifugal interchange instability. Issue 7 (23rd July 2013) - Winglee, R. M.; Kidder, A.; Harnett, E.; Ifland, N.; Paty, C.; Snowden, D.
Abstract: [1] The origin of the periodicities in the radio, plasma, and magnetic fields of Saturn has long been debated. Given the high degree of alignment of Saturn's dipole with its rotation axis, no strong rotational periodicities are expected. However, Cassini data demonstrated the existence of such periodicities not only in Saturn's kilometric radio emissions (SKR) but in the plasma and magnetic field signatures. It is shown that the development of the centrifugal interchange instability that originates from mass loading from the Enceladus torus contains information about the planetary rotation period. However, the planetary period is masked by high‐frequency components of the instability. The presence of Titan is shown to damp the high‐frequency components and enables the fundamental frequency near the planetary rotation frequency to grow at the expense of the high‐frequency components. As a result, the interchange instability is seen to change from one where five to seven large interchange fingers dominate to one where there are about three which cause the modulation of magnetospheric parameters near the planetary period. This modulation includes the movement of the magnetopause, the injection of energetic particles into the inner magnetosphere and the plasma density at high latitudes, both of which control SKR. Controlling factors on the frequency include Titan's drag on the plasma sheet which produces asymmetries between the Northern and Southern Hemispheres, solar wind conditions, and the density of the Enceladus plasma torus. The resultant magnetic perturbations are shown to have similar size and frequency as that seen in Cassini data. Key Points: Saturn's periodicity driven by magnetospheric processes Interchange instability modified by Titan's interaction is the source Able to describe several features without ad hoc assumptions